I am a cat - Bernstein, Galia (New York : Abrams Books for Young Readers, 2018)
Simon the housecat points out that he may not roar like a lion or run fast like a cheetah, but he has many other things in common with the big cats.
Keywords: Cats -- Juvenile fiction; Felidae -- Juvenile fiction; Cats -- Fiction; Cat family (Mammals) -- Fiction; Size -- Fiction